Assessment of nitrogen and phosphorus of treated effluents from slaughterohouses in the city of Pelotas/RS - Rodrigues, Daniel Lucas Costa; Hartwig, Marcelo Peske; Gerber, Michel David (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The flesh agroindustrial sector is of great economic importance in Rio Grande do Sul, however this activity is also recognized by the high pollution potential. Considering the difficulties to fulfill the stringent nitrogen and phosphorus emission standards, this study aimed to assess the treated effluents of four slaughterhouses of the region of Pelotas/RS, relating them to the emission standards established by CONSEMA Resolution number 128/2006, after four years of the end of the period prescribed by law. All assessed companies fulfill the established discharge standard for phosphorus, but in relation to the KTN parameter, only 50% of the assessed companies fulfilled what is recommended by law, by concentration or by minimum removal efficiency. The results also indicated that two slaughterhouses must continue investing in the effluents treatment system to fulfill the applicable environmental law.